The Process and Outcomes of Learning Natural and Social Sciences through Numbered Heads Together: Proses dan Hasil Belajar Ilmu Pengetahuan Alam dan Sosial melalui Numbered Head Together - Afindah, Nur; Megawati; Dani, Refril (Indonesian Journal of Innovation Studies, 2025)
General background: Quality science learning in elementary schools often declines when dominated by teacher-centered methods, limiting students’ critical and collaborative engagement. Specific background: At SDN 178/II Purwasari, sixth-grade IPAS lessons showed low achievement, with only 43.4% of students meeting the minimum criteria. Knowledge gap: While cooperative models such as Numbered Head Together (NHT) have been widely studied, few have examined their effectiveness in IPAS within the Kurikulum Merdeka context, which emphasizes inquiry and 21st-century competencies. Aim: This study investigates the implementation of the NHT model to enhance learning processes and outcomes in grade VI IPAS. Results: Using a classroom action research design over two cycles with 23 students, findings revealed improvements in teacher performance (81.2% to 100%), student engagement (65.7% to 83.6%), and learning mastery (43.4% pre-cycle; 73.9% cycle I; 82.6% cycle II). Novelty: Unlike prior studies on single-subject applications, this work demonstrates the integration of NHT in IPAS as an interdisciplinary subject aligned with Kurikulum Merdeka. Implications: The study highlights NHT’s potential to foster critical thinking, collaboration, and responsibility, offering a practical pedagogical strategy to support national curriculum reforms and improve elementary science education. Highlights: • Teacher performance improved from 81.2% to 100%• Student participation increased from 65.7% to 83.6%• Learning mastery rose from 73.9% to 82.6% Keywords: Numbered Head Together, Learning Process, Learning Outcomes, Science Learning, Grade VI